Power and methanol production from biomass combined with solar and wind energy: analysis and comparison. (July 2018) - Firmansyah, Husni; Tan, Yuting; Yan, Jinyue
Abstract: This study addresses the techno-economic analysis and comparison of systems for power and methanol production from biomass combined with solar and wind energy, from both technical and economic perspectives. Three different systems, based on Integrated Gasification Combined-Cycle (IGCC), Oxy-fuel combustion, and syngas gasification, were evaluated. The hydrogen required for methanol production comes from water electrolysis driven by solar and wind energy. In addition, the effect of location was discussed.